2018
DOI: 10.1080/07380577.2018.1526434
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in Research and Development Projects Among Community-working Occupational Therapists in Norway

Abstract: A cross-sectional descriptive survey was conducted (n = 561). Almost half of the participants took part in research and development projects. Being involved in research and development was associated with lower age, having further education, and higher levels of work experience. The current and prioritized research topics were reablement and assistive technology. The study implies that community-working occupational therapists are largely involved in research and development, or eager to become involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The development of professional practice was the focus of a study that presented a cross-sectional descriptiv research and development projects (Bonsaksen et al, 2018), which included occupational therapy services an 'restorative care', which is more commonly used in the USA, and describes home-based, goal-oriented interve elderly with functional decline" (Bonsaksen et al, 2018: 2).…”
mentioning
confidence: 99%
“…The development of professional practice was the focus of a study that presented a cross-sectional descriptiv research and development projects (Bonsaksen et al, 2018), which included occupational therapy services an 'restorative care', which is more commonly used in the USA, and describes home-based, goal-oriented interve elderly with functional decline" (Bonsaksen et al, 2018: 2).…”
mentioning
confidence: 99%
“…A previous study based on the same data showed that having further education was positively associated with involvement in research and development. 18 Thus, associations between education level, research involvement and perceived influence appear to align with rational choice theory. 15-17 As derived from this view, increasing one’s education level and becoming involved in research and development projects may be guided by a motivation to secure and strengthen one’s opportunities in current and future employments.…”
Section: Discussionmentioning
confidence: 64%
“… 26 , 31 , 32 Moreover, municipalities with more OTs can offer a higher degree of internal specialisation, which, in turn, might increase both the number of OT positions, and help to recruit attractive candidates. 17 The emerging picture suggests that the establishment of OT-positions could indicate the starting point for an upwards-spiral, through which both availability and quality of OT-services increases through better knowledge, and more relevant tasks for community-based OT-services. 17 , 34 This might imply major benefits for the communities-in-question; however, this also implies challenges with health equity if some municipalities are ‘left behind’ in respect to this development.…”
Section: Discussionmentioning
confidence: 99%